Deep‐sea corrosion rusticles from iron‐hulled shipwrecks. Issue 7 (18th March 2021) - Silva‐Bedoya, Lina M.; Watkin, Elizabeth; Machuca, Laura L.
Abstract: Vertical tube‐shaped iron‐oxide accumulations, named rusticles, obtained from the wrecks of the HMAS Sydney II and the HSK Kormoran at 2480 m ocean depth were chemically analysed along with surrounding seawater. Rusticles consisted of a porous aggregation of iron oxides and high levels of toxic metals and metalloids. Their growth rate is approximately 1 cm per year, predominantly over the areas of the hulls that remained underwater during their service years. A connection between the quality of antifouling paints and rusticle growth and composition was found. A mechanism explaining the formation of rusticles is proposed based on corrosion of carbon steel in deep‐seawater, water chemistry, surface complexation of iron oxides and chemical garden formation mechanisms. This study provides a complete rationalisation of the process of rusticle formation and deep‐water corrosion that is applicable to the long‐term integrity of offshore infrastructure. Abstract : Coating or surface defects followed by localised corrosion are the initial steps of rusticle development. Deep‐seawater chemistry and hydrostatic pressure play major roles in the development of rusticles. The degree of water saturation of the different structures of the ships during their service life has a direct relationship with rusticle abundance. The microstructures present in the rusticles evidence the enormous surface area the rusticles have to interact/react with the environment.